Effect of Educational Intervention on Awareness and Attitude regarding Voluntary Blood Donation among Rural People: A Quasi- Experimental Study - Goyal, Palak; Kumar, Amit; Khan, Huma; Kumar, Ravi (Indian Journal of Community Health, 2023)
Donation of blood has always been considered as Humanitarian act. Despite the increasing demands for blood and its products, many people have little interest in donating blood. We undertook this study to assess the level of knowledge & attitude and to assess the effect of awareness talk regarding voluntary blood donation among rural people. Information from attendants of the patients visiting the Telemedicine Centre was collected using the Predesigned Pretested Semi open ended Interview Schedule. Out of 108 study subjects, 83 (76.8%) of study subjects didn’t knew their blood group. 52 (48.1%) said women cannot donate blood while they are pregnant or lactating. After the awareness talk, 78 (72.2%) were motivated for voluntary blood donation. There should be more awareness activities to promote voluntary blood donation in public.